BLOOD COAGULATION POTENTIAL IN PATIENTS WITH MYOCARDIAL INFARCTION AFTER THROMBOLYSIS AND POSSIBILITIES OF ITS CORRECTION USING MAGNETOTHERAPY - Zolotaryova, N.A.; Vastyanov, R.S.; Panigrahi, P.K.; Grigoriev, E.O.; Ostapenko, I.O. (World of Medicine and Biology, 2024)
The purpose of the study was to investigate the magnetotherapy efficacy aimed at blood coagulation potential and fibrinolytic activity improvement in patients with acute myocardial infarction with ST-segment elevation after thrombolysis at the inpatient stage of rehabilitation. 80 patients with acute myocardial infarction with ST-segment elevation were included in the clinical observation. These patients were randomized into 2 groups. Group 1 consisted of 40 patients treated using thrombolytics with adjuvant therapy and standard cardiovascular drugs. Group 2 consisted of 40 patients who were additionally prescribed the course of magnetotherapy. All patients’ blood coagulation potential was analyzed, including the coagulative and anticoagulative chains and fibrinolytic activity standardized indexes. The data obtained showed that parameters of hemostasis quickly return to normal values in patients with acute myocardial infarction with ST-segment elevation 2–3 days after thrombolytic therapy and heparin administration that demonstrate combined moderate blood procoagulative system activation against the background of both anticoagulative and fibrinolytic systems reduced activity. The developed tendency to hypercoagulation duration is maintained throughout the entire inpatient period reaching maximum before the patients’ discharge. The course of magnetotherapy in the complex treatment of patients with acute myocardial infarction with ST-segment elevation stimulates a favourable impact on hemostasis coagulative and anticoagulative systems imbalance toward its coagulative potential reduction and fibrinolytic activity increase. The authors suppose that the original magnetotherapy method is easy to perform, effective in blood hypercoagulative state reduction, does not induce side effects, and can be recommended to patients with acute myocardial infarction with ST-segment elevation of any age and weight category after thrombolytic therapy.